For perpendicular lines, m2 = -1/m1; where m1 is the slope of line 1 and m2 is the slope of line 2.
m1 = (-4 - 2)/(4 - 2) = -6/2 = -3
m2 = -1/-3 = 1/3
Equation of the required line is given by: y - 4 = 1/3 (x - (-1))
y - 4 = 1/3 x + 1/3
y = 1/3 x + 1/3 + 4
y = 1/3 x + 13/3
Answer:
The terms are not equivalent
Step-by-step explanation:
-8 - 2(3+2n)+7n
Distribute the 2
-8 -6-4n+7n
Combine like terms
-14 +3n
That is not equal to -30 -13n
The terms are not equivalent
1/6 = 0.16 with a line over the 6 because it is repeating
-3 (x - 5) - 8 (y + 2) + (-3) (6 - 4b)
First, simplify your brackets. / Your problem should look like: -3 (x - 5) - 8 (y + 2) + -3 (6 - 4b)
Second, simplify. / Your problem should look like: -3 (x - 5) - 8 (y + 2) - 3 (b - 4b)
Third, expand your problem. / Your problem should look like: -3x + 15 - 8y - 16 - 18 + 12b
Fourth, simplify. / Your problem should look like: -3x - 8y + 12b - 19
Answer: -3x - 8y + 12b - 19 (D)